Vitamin E and essential polyunsaturated fatty acids supplementation in schizophrenia patients treated with haloperidol. (20th April 2016) - Bošković, Marija; Vovk, Tomaž; Koprivšek, Jure; Plesničar, Blanka Kores; Grabnar, Iztok
Abstract : Objectives : Previously, oxidative damage has been associated with severity of clinical symptoms and supplementation with antioxidants and essential polyunsaturated fatty acids (EPUFAs) was proposed to have beneficial effects in schizophrenia. We evaluated the effects of supplementation with EPUFAs and vitamin E in patients treated with haloperidol depot injection. Design : This was a double-blind randomized placebo-controlled study with four arms (Placebo, vitamin E, EPUFAs, and vitamin E + EPUFAs). Biomarkers of oxidative stress, neurochemistry, psychopathology, and extrapyramidal symptoms were assessed at baseline and after 4 months. Results : In EPUFAs group of patients, reduced glutathione concentration was increased compared to placebo. Concentration of oxidized glutathione was decreased in patients receiving vitamin E. In addition, compared to placebo a non-significant trend of increased activity of catalase and superoxide dismutase was observed in all three treatment groups. Patients receiving vitamin E experienced less motor retardation. No difference in extrapyramidal symptoms was found. Discussion : Our study indicates that supplementation with vitamin E and EPUFAs may improve the antioxidative defense, especially glutathione system, while there is no major effect on symptoms severity. Supplemental treatment with EPUFAs and vitamin E in schizophrenia patients treated with haloperidol is potentially beneficial and a larger independent study appears warranted.